VD_FINDINFO HC / 2011 / 162 vom 23. März 2011 - VD Tribunal cantonal (2011)
DROIT DE GARDE, AUTORITÉ PARENTALE, PROTECTION DE L'UNION CONJUGALE | 176 al. 3 CC, 308 al. 1 let. b CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH)